Covey's principle centered leadership : its applicability to the leadership and management of Islamic schools in Malaysia - Nor Zalmiah Jahidin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1999)
This study explore the possibility of incorporating Covey's Principle Centered Leadership (PCL) in the leadership and management of Islamic schools in Malaysia. It is hoped that, by incorporating principles of effective leadership and management as advocated by Covey in PCL would help overcome the prevalent weaknesses in the administgration of Islamic schools. The significance of Covey's PCL is first established. Covey's comprehensive eview of man's needs supported by his principle centered management paradigm proves superior to the existing, mainly positivistic paradigms. Expounding Covey's PCL in great depts unravels very close resemblance to some Islamic principles of leardership and management. An analysis of Covey's PCL in the light of Islamic perspective exposes its simillarities, strengths and weaknesses. Consequently, incorporation and application measures of Covey's PCL in the leadership and management of Islamic schools is next discussed. The study employs and analytical qualititative methodology. Textual and documentary analysis were also conducted. Principles of leadership and management were explored and compared between Covey's PCL and the Islamic sources from mainly the Qur'an and Hadith. In addition, Sirah (the biography) of the Prophet (s.a.w) and the Islamic administrative practices, particularly those of the Khulafah ar-Rashidun provide further insights. The sutdy contends that it is timely that the leadership and management of Islamic schools in Malayhsia take priority due to their wanting state of affairs. Should the ummah (Muslim community) decide to create or repeat the history of the glorious period of Islam, it is imperative to start with the school, the nurturing place of young Muslims. Effective leadership and management will help realize the vision. The study points out that Muslims should inculcate the spirit of pursuing knowledge and thereby uncover wisdom, for it is their lost property. On the basis of ijtihad (independent legal judgement) and siyasah shari'ah (the shari'ah politics), Muslims must venture into new ideas to discover means and wayhs that would help enhance Muslims' performance. Finally, the study recommends among other things, that leadership and management of Islamic schools i) espouse a school mission and vision, ii) have a set of values and principles iii) set forth a module to develop character and competence of staff, iv) develop a set of programs and activities to foster relationships and hence trust among staff, and v) adopt empowerment process and decision making process based on shura (mutual consultation).